Waning immunity, prevailing non-vaccine type ptxP3 and macrolide-resistant strains in the 2024 pertussis outbreak in China: a multicentre cross-sectional descriptive studyResearch in context - Jiehao Cai; Qiyi Liu; Biquan Chen; Yue Jiang; Xiaoyan Zeng; Jiebin Huang; Daojiong Lin; Huanyou Li; Jinqiang Zhang; Zhiqiang Zhuo; Yanping Zhang; Panpan Lv; et al. (The Lancet Regional Health. Western Pacific)
Summary: Background: In the spring and summer of 2024, an unexpected large outbreak of pertussis hit China, with the annual incidence of pertussis (34.03/100,000) more than 12-fold higher than that of 2023 (2.71/100,000). We aimed to assess clinical and molecular epidemiological patterns and unravel the reasons behind the 2024 pertussis outbreak. Methods: PCR-confirmed pertussis cases were enrolled from five sentinel hospitals in Shanghai, Anhui, Hainan, Fujian, and Inner Mongolia between 1 January and 30 September 2024. The epidemiological data of PCR-confirmed cases, as well as the clinical data and vaccination history of hospitalized cases were collected. Nasopharyngeal swab samples were collected from partial pertussis cases and their household contacts for Bordetella pertussis culture during the local peak months. Antimicrobial susceptibility testing and whole genome sequencing were performed on all 394 isolates to evaluate six antibiotic susceptibility and characterize the antigenic, virulent, and phylogenetic characteristics of the circulating isolates. Findings: A total of 14,874 cases of pertussis were PCR-confirmed in the 5 sentinel hospitals, peaking in April to July. Infants represented 9.6% of cases and children aged 4–10 years represented 74.3% of cases in the five hospitals. Of the 7238 (48.7%) cases with vaccination data, 6563 (90.7%) were fully vaccinated. Breakthrough pertussis cases were mainly observed in fully vaccinated children since the age of 7 months. Among the 828 (5.6%) cases hospitalized for pertussis, 71.7% (594/828) cases had complications (pneumonia 69.7%, 577/828), 5.7% (47/828) were admitted to intensive care unit and 0.24% (2/828) cases died. Sixty-four per cent (403/630) of families had both the patient and at least one family member PCR-positive for B. pertussis. In total, 394 B. pertussis isolates were recovered from the 1921 nasopharyngeal swab samples. Ninety-nine point seven per cent (393/394) of isolates displayed high-level resistance to azithromycin (MIC range, 16–256 μg/ml), and 48.0% (189/394) isolates were susceptible to trimethoprim-sulfamethoxazole (MIC range, <0.008/0.152–0.5/9.5 μg/ml). All the isolates were susceptible to levofloxacin, doxycycline, ceftazidime, and cefoperazone/sulbactam. All the isolates were assigned to ST-2 and 99.5% (392/394) belonged to the MT28-Shanghai clone by SNP-based analysis, carrying ptxP3 AgST4, 23S rRNA-13 (with erythromycin resistance), and prn150. 23.4% (92/394) of isolates were predicted to be PRN-deficient. Interpretation: The waning vaccine-derived protection and the prevailing macrolide-resistant MT28 clone harboring non-vaccine type ptxP3 are responsible for the 2024 large outbreak of pertussis in China. Our findings highlight the urgent need for revising national pertussis vaccination strategies and traditional first-line antibiotic therapy. Booster vaccination for children aged 4–6 years is urgent to control the pertussis outbreak. Funding: This work is supported by Shanghai Municipal Sixth Round Three-Year Action Plan for Strengthening the Construction of the Public Health System (GWVI-11.1-07, GWVI-2.1.2) and National Natural Science Foundation of China (82272381).